2010
DOI: 10.4103/0974-2077.63286
|View full text |Cite
|
Sign up to set email alerts
|

Double dart technique of instillation of triamcinolone in ganglion over the wrist

Abstract: Background:Ganglia are the most common benign cystic swellings found over both the dorsal and volar aspects of the wrist. In spite of technical advancement, both operative and non-operative interventions achieve more or less similar results. Complete evacuation of gelatinous fluid followed with intra cystic instillation of triamcinolone has given encouraging results.Aims:To assess the efficacy and safety of drainage of cyst and instillation of triamcinolone in wrist ganglion.Materials and Methods:A prospective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 13 publications
1
14
1
Order By: Relevance
“…In the two-year observation period, ganglion recurrence was noted in eight out of the 105 patients in the group treated with aspiration (8.4%) and in 14 out of the 114 patients who were treated surgically (12.2%). In this study no adverse effects, including skin hypopigmentation, were observed after administration of triamcinolone [17]. This was in contrast to the aforementioned study by Chatterjee et al [10], who reported hypopigmentation in five out of 60 patients (8.3%) who were treated with triamcinolone.…”
Section: Steroidscontrasting
confidence: 87%
See 3 more Smart Citations
“…In the two-year observation period, ganglion recurrence was noted in eight out of the 105 patients in the group treated with aspiration (8.4%) and in 14 out of the 114 patients who were treated surgically (12.2%). In this study no adverse effects, including skin hypopigmentation, were observed after administration of triamcinolone [17]. This was in contrast to the aforementioned study by Chatterjee et al [10], who reported hypopigmentation in five out of 60 patients (8.3%) who were treated with triamcinolone.…”
Section: Steroidscontrasting
confidence: 87%
“…Local adverse effects can result from both the properties of a given chemical substance and an incorrect injection technique. Many authors have proposed specific injection techniques to minimize the risk of injecting the chemical substance in an inappropriate location [10,15,17].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Surgery offers higher success rates in most series [2]. Surgical excision is effective, with a recurrence rate of around 5% if care is taken to completely excise the stalk of the cyst along with a small portion of joint capsule-The recurrence rate may vary from 1% (Angilides et.al) to 49% (Zachariae et.al) [2] Aspiration with intralesional steroid, with its many advantages, may be an alternative choice for the patient if the success is comparable to surgical excision [3,4].…”
Section: Introductionmentioning
confidence: 99%